P1 An analysis of 8, 503 cases of mesothelioma from the National Lung Cancer Audit. (14th November 2013) - Beckett, P; Woolhouse, I; Stanley, R; Fennell, D; Edwards, J; Hubbard, R; Peake, MD
Abstract : Background: The National Lung Cancer Audit records outcomes in lung cancer and mesothelioma on a population scale, in order to explain the wide variations seen within the UK and between the UK and other countries and ultimately improving outcomes. Methods: All cases of mesothelioma submitted to the audit by English Trusts 2006–2011 were analysed. A hierarchy of diagnosis from surgical histology to non-surgical histology to clinical diagnosis was used to exclude patients with potentially conflicting diagnoses. These records were further analysed to extract data on age/sex distribution, referral source, histological subtype, treatment regime and survival rates. Results: There were 8, 503 patients with mean age 72yrs (83% male), representing around 65% of expected incident cases (a substantial number diagnosed at autopsy and not included in the audit). 45% have right-sided disease, 28% left-sided, and 1% bilateral (data missing in 26%). The majority of patients (47%) were referred by their primary care physician, but at least 20% present to secondary care as emergencies. Overall, 89% were histo-cytologically confirmed with that figure appearing to rise slowly over the audit period from 81% (2006) to 92% (2011). Survival data is shown in the table. 37% of patients received no anti-cancer treatment, but 28%, 26% and 30% of patients received "surgery", chemotherapy or radiotherapy at any time. Most surgical operations (60%) were pleurodesis. Median survival varied by first treatment modality: surgery 378 days, chemotherapy 399 days, radiotherapy 308 days, no anti-cancer treatment 140 days. Survival was highest in patients having "surgery" and chemotherapy (491 days). Use of chemotherapy varied across cancer networks from 14% to 41% of patients, but overall increased over the audit period from 13% to 34%. Conclusion: Mesothelioma is predominantly a cancer of elderly males, with a striking tendency for right-sided disease. Only 11% have no histological confirmation, but where this is obtained, the epithelioid subtype has best prognosis. Low rates of anti-cancer treatment may reflect therapeutic nihilism as well as patient fitness, but there is an encouraging trend towards wider use of chemotherapy which was associated with a greater than doubling in survival compared with no treatment.